2 Factors affected dental health care behaviors of parents for young children In Saraphi district Chiang Mai province in 2006. - เดชะวัชรีกุล นิมิต (Thai Dental Public Health Journal, 2019)
The purpose of this study was to investigate the dental health care behavior of parents for 2-3 year children at Saraphi district, Chiang Mai province, and factors which affected the dental health care behaviors of parents including dental caries status of early childhood. Sample size consisted of 205 cases, chosen through multi-stage sampling procedure. The samples were interviewed by questionnaire. The statistics used to analyze the data were frequency, percentage, mean, standard deviation, Pearson Correlation and stepwise multiple regression analysis. The findings showed that young children had dental caries status about 27.3 percent and mean deft was 0.89 teeth per person. The dental health care behaviors of parents of 2-3 year old children at Saraphi district, Chiang Mai province were satisfactory on oral cleaning behavior, feeding pattern behavior, and oral examination by parents, but oral health consultation visit behavior was unsatisfactory. It was found that social support, mass media information and receiving toothbrushes were significantly affected dental health care behaviors. The factors in the order of their importance were social support, mass media information, receiving toothbrush for kids that affected the dental health care behaviors respectively.